Indicadores de financeirização nas empresas com maior valor de mercado - Carmo, Marcelo José do (Universidade Federal de São Carlos, 2020)
The economic process of financialization is considered by several authors as the development of dependence and subordination of productive capital to financial capital. Besides, financialization is also considered as a change in the conception of control of firms, in force today, for which the maximization of shareholder value becomes the main concern. In this doctoral work, we set out to analyze the financialization indicators in the ten companies with the highest market capitalization worldwide, through multi-case research and an exploratory approach. We did not intend to exhaust the debate on financialization or explain everything that happens in companies, but rather to develop the construction of indicators, from the perspective of Economic Sociology. Some indicators that makeup financialization can be highlighted, such as 1) Comparison between the sources of profitability; 2) Shareholding Composition and Shareholding Acquisitions. 3) Mergers and Acquisitions; 4) Origin of the directors; 5) Payment of Compensation to Executives; 6) Payment of Dividends to Shareholders 7) Employee Salaries and 8) Employment. Preliminarily, we have already found that the services or financial services segment has constituted an important fraction of the profitability of some companies, exceeding production profits. The shareholding structure of companies and shareholding acquisitions are increasingly in charge of large investment funds and financial institutions, which already surpass the largest banks in market cap. The managers of the companies, even those who came from an academic background focused on the industry, make decisions that are very attuned to the financialized mentality, with the payment of millionaire compensation to executives, reinforcing the expansion of a layer of wealthy managers. Dividends and stock buybacks have been draining almost all of the companies' net income, making them work emphatically to pay dividends to shareholders. This is a significant qualitative change over the past forty years, which has been transforming the production area towards creating shareholder value. Meanwhile, the salaries of most employees are below the average salary of all ethnic groups in the USA, for example, as we will see. The level of employment is also an indicator of financialization, sometimes dropping dramatically, now increasing, as in the cases of Amazon and Apple, which have created thousands of jobs in recent years, but through cheaper labour through outsourcing. In this work we have analyzed the ten companies with the highest market capitalization worldwide, applying the eight indicators described above. With this debate, we hope to contribute to the research agenda of economic sociology and finance, through empirical research and its analysis in the light of the existing theoretical production.
Financialization indicators in companies with the highest market capitalization
Keywords: Financeirização; Indicadores; Empresas contemporâneas; Sociologia econômica; Teoria das organizações; Financialization; Indicators; Contemporary companies; Economic sociology; Organization theory; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO